Propagation of nonlinear wave in 2-D planar and axisymmetric non-ideal radiating gas flow under the influence of magnetic field - Srivastava S.K.; Chaturvedi R.K.; Singh L.P. (My University, 2025)
Influence of magnetic field on the propagation of shock waves in radiation gasdynamics is analysed by using wavefront analysis method. We examined behavior of the waves propagated into the two-dimensional (2-D) steady supersonic magnetogasdynamic flow of non-ideal gas with radiation. The transport equations are derived, which determine the condition for the shock formation. The effect of non-idealness and thermal radiation and their consequences under the influence of magnetic field is studied and examined how the flow patterns of the disturbance vary with respect to the variation in the parameters of the flow. It is found that the presence of a magnetic field plays an essential role in the wave propagation phenomena. Nature of the solution with respect to Mach number is analysed, and it is examined how the shock formation distance changes with an increase or decrease in the value of Mach number. Also, the effect of non-idealness on the shock formation distance is elucidated and examined how the shock formation affects the increase in the value of non-ideal parameter in the presence of magnetic field with thermal radiation. © 2023, Indian Academy of Sciences.